CONSIDERATIONS ON THE ESSAY GENRE (American Journal of Pedagogical and Educational Research, 2023)
This article talks about essay genre and its features, essay writing rules, the importance of being able to write an essay for a young professional, developing independent creative thinking skills through an essay, the structure and plan of an essay.